464 TGFβ 1 AND THROMBIN REGULATE α-SMOOTH MUSCLE ACTIN, MMP3 AND TIMP3 MRNA ACCUMULATION IN MURINE PLACENTAL FIBROBLASTS. (1st January 2005) - Moghimi, A.; Piroozi, A.; Honrubia, D.; Bertolotto, C.; Ubal, V.; Acuna, D.; Knauer, Y.; Wang, C.; Yang, G.; Tan, Y; Simmons, C. F.
Abstract : Background: Myofibroblasts are specialized mesenchymal cells that contribute to developmental fibrotic disorders, including placental fibrosis associated with intrauterine growth restriction. TGFβ1 and thrombin, released during thrombosis, stimulate the differentiation of myofibroblasts in many tissues. TGFβ1 and thrombin promote proliferation and migration of mesenchymal cells, synthesis and deposition of extracellular matrix (ECM), and inhibition of proteolytic enzymes that degrade ECM. MMP3 (Stromelysin-1) and its inhibitor, Timp3, are among major enzymes that are involved in ECM degradation and remodeling. We have developed a transgenic mouse line expressing EGFP (enhanced green fluorescent protein) in myofibroblasts, under the control of an α-smooth muscle actin enhancer/promoter. Fibroblasts were cultured from placental tissue, conditionally immortalized with an SV40T plasmid, and cloned. Objective: We hypothesize that TGFβ1 and thrombin stimulate placental myofibroblast differentiation and subsequent, coordinate MMP3 and Timp3 mRNA regulation. Design/Method: Control, TGFβ1 (10 ng/ml), and thrombin (0.5 U/ml) exposed placental fibroblasts were studied up to 24 hours in cell culture. Cells underwent RNA extraction, cDNA synthesis, and microarray analysis utilizing an Affymetrix chip array (MOE 430A). We quantitated, in duplicate, mRNA accumulation of α-smooth muscle actin (α-SMA), MMP3 and Timp3. Results: TGFβ1 and thrombin induced differentiation of fibroblasts to myofibroblasts. α-SMA mRNA accumulation was increased 7 fold and 1.7 fold by TGFβ1 and thrombin, respectively, vs. control. MMP3 mRNA accumulation decreased by 2.3 fold and 1.3 fold, whereas Timp3 mRNA accumulation was upregulated 3.9 fold and 1.7 fold, respectively, vs. control. This differential mRNA expression is being confirmed by RT-PCR, and protein expression analyzed by Western blot and immunofluorescence. Conclusion: These results demonstrate TGFβ1 and thrombin induce differentiation of placental fibroblasts to a unique myofibroblast phenotype. In addition, these ligands, released locally during thrombus formation, may influence placental structure and function by promoting a fibrotic state consisting of increased ECM synthesis and reduced ECM degradation.